Roles of Hcp family proteins in the pathogenesis of the porcine extraintestinal pathogenic Escherichia coli type VI secretion system - Peng, Ying (Sci Rep, 2016)
Hcp (hemolysin-coregulated protein) is considered a vital component of the functional T6SS (Type VI Secretion System), which is a newly discovered secretion system. Our laboratory has previously sequenced the whole genome of porcine extraintestinal pathogenic E. coli (ExPEC) strain PCN033, and identified an integrated T6SS encoding three different hcp family genes. In this study, we first identified a functional T6SS in porcine ExPEC strain PCN033, and demonstrated that the Hcp family proteins were involved in bacterial competition and the interactions with other cells. Interestingly, the three Hcp proteins had different functions. Hcp2 functioned predominantly in bacterial competition; all three proteins were involved in the colonization of mice; and Hcp1 and Hcp3 were predominantly contributed to bacterial-eukaryotic cell interactions. We showed an active T6SS in porcine ExPEC strain PCN033, and the Hcp family proteins had different functions in their interaction with other bacteria or host cells.